Implementasi Kreativitas Guru dalam Meningkatkan Motivasi Belajar Bahasa Arab di Madrasah Aliyah Riyadhul Jannah - Ratna Listi; Yeni Nuriah Fitri (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aimed to describe the implementation of teacher creativity in Arabic language learning, analyze its contribution to students' learning motivation, and identify the supporting and inhibiting factors influencing its implementation at Madrasah Aliyah Riyadul Jannah. The study employed a qualitative approach using a case study design. The participants consisted of two Arabic language teachers and fifteen students selected through purposive sampling. Data were collected through classroom observations, in-depth interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings revealed that teacher creativity was reflected in the use of varied teaching methods, instructional media, and learning activities adapted to students' characteristics, resulting in more active, communicative, and meaningful learning experiences. Teacher creativity also contributed to strengthening students' learning motivation by increasing participation, engagement, and self-confidence. Its implementation was supported by pedagogical competence, professional reflection, and a supportive school environment, although differences in students' abilities and limited instructional time remained significant challenges. These findings indicate that teacher creativity functions as a pedagogical process that strengthens the quality of Arabic language learning while fostering students' learning motivation.